2008
DOI: 10.2478/v10045-008-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Effects of Trichoderma Species in Biocontrol of Armillaria Mellea in Fruit Trees in Iran

Abstract: Root and butt rot caused by species of Armillaria is one of the most serious diseases of fruit and forest trees in Iran. In this study, antagonistic effects of Trichoderma in biocontrol of Armillaria were investigated. Armillaria mellea was isolated from infected roots and butts of cherry and almond trees and identified with pairing tests method. Trichoderma species were recovered from rhizomorphs and around soil of Armillaria infected roots. Trichoderma species identified were T. virens (nine isolates) and T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
1
11
0
2
Order By: Relevance
“…This may be due to a "crowding effect" phenomenon that occurs when the spore populations of antagonistic fungi are too high, as was previously reported by Chitarra (2003) The results of the previous studies have also shown that biological control agents are effective against damping-off, root rot, and wilt diseases of ornamental plants, vegetables and cereals, caused by Rhizoctonia, Pythium, Phytophthora, Sclerotium, Fusarium and some other fungi (Whipps 2001;Asef et al 2008;Naraghi et al 2010a, b, c;Godhani 2011;Ojaghian 2011).…”
Section: Discussionmentioning
confidence: 86%
“…This may be due to a "crowding effect" phenomenon that occurs when the spore populations of antagonistic fungi are too high, as was previously reported by Chitarra (2003) The results of the previous studies have also shown that biological control agents are effective against damping-off, root rot, and wilt diseases of ornamental plants, vegetables and cereals, caused by Rhizoctonia, Pythium, Phytophthora, Sclerotium, Fusarium and some other fungi (Whipps 2001;Asef et al 2008;Naraghi et al 2010a, b, c;Godhani 2011;Ojaghian 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Under greenhouse conditions, Jakubikova et al (2010) pointed out that T. harzianum isolates with an inhibition rate of 21-68% toward the pathogenic virus (BNYVV). The results of the previous studies have also shown that BCAs are effective against damping-off, root rot, and wilt diseases of ornamental plants, vegetables and cereals (Whipps, 2001;Asef et al, 2008;Naraghi et al, 2010a, b, c;Godhani, 2011;Ojaghian, 2011).…”
Section: Resultsmentioning
confidence: 93%
“…Varias especies de Trichoderma han sido ampliamente estudiadas como ACB. Uno de los principales atributos de este género es la alta tolerancia a cambios ambientales lo que le permite competir y antagonizar a algunas especies de patógenos fúngicos (Reza Asef et al 2008).…”
Section: Resultados Y Discusiónunclassified